Agroforestry: a second soil fertility paradigm? a case of soil fertility management in Western Kenya - Mango, Nelson; Hebinck, Paul (Informa UK Limited, 2016)
This paper explores the claim whether agro-forestry is a second soil fertility paradigm. The answer to this question, however, is not unequivocal. Farmers in Western Kenya generally do not apply fertiliser and rather rely on many soil fertility replenishment (SFR) strategies. Scientists recognised that lowering the costs of restoring fertility is vital to the future of agriculture in the region and beyond. Agroforestry emerged as an alternative strategy to replenish soil fertility and has been introduced through various programmes and institutions in Western Kenya since the early 1990s. Detailed field and case studies show that people are indeed convinced that agro-forestry helps them to replenish soil fertility and that over the years yields indeed have increased. The paper also traces the emergence of localised practices (niches) of soil fertility management. These niches stand for local ways of reproducing soil fertility. These practices coexist with improved fallows, and mutually transform each other through various kinds of interactions at field and village level as well as with technology institutions. Together they reflect the diversified soil fertility options that resonate well with the multiple nature of nutrient and other soil constraints. Low-cost technologies for supplying nutrients to crops are needed on a scale wide enough to improve the livelihood of farmers. The aim of the paper is to show whether and how externally induced improved fallow innovations resonate with farmer-produced niches in the domain of SFR in Luoland. The paper contributes in this way to a more appropriate understanding of socio-technical innovations.